The potential of Antheraea pernyi silk for spinal cord repair. Issue 1 (December 2017) - Varone, A.; Knight, D.; Lesage, S.; Vollrath, F.; Rajnicek, A.; Huang, W.
Abstract One of the most challenging applications for tissue regeneration is spinal cord damage. There is no cure for this, partly because cavities and scar tissue formed after injury present formidable barriers that must be crossed by axons to restore function. Natural silks are considered increasingly for medical applications because they are biocompatible, biodegradable and in selected cases promote tissue growth. Filaments from wildAntheraea pernyi silkworms can support axon regeneration in peripheral nerve injury. Here we presented evidence that degummedA. pernyi filaments (DAPF) support excellent outgrowth of CNS neuronsin vitro by cell attachment to the high density of arginine-glycine-aspartic acid tripeptide present in DAPF. Importantly, DAPF showed stiffness properties that are well suited to spinal cord repair by supporting cell growth mechano-biology. Furthermore, we demonstrated that DAPF induced no activation of microglia, the CNS resident immune cells, eitherin vitro when exposed to DAPF orin vivo when DAPF were implanted in the cord.In vitro DAPF degraded gradually with a corresponding decrease in tensile properties. We conclude thatA. pernyi silk meets the major biochemical and biomaterial criteria for spinal repair, and may have potential as a key component in combinatorial strategies for spinal repair.